Staphylococcus epidermidis necrotizing pneumonia and pneumatocele in a term infant - Johan AJ,; Cheah FC, (Penerbit UKM, 2009)
Staphylococcus epidermidis is emerging as an increasingly important pathogen in the immunocompromised host. We report here a case of S. epidermidis necrotizing pneumonia complicated by pneumatoceles in a term male infant who had earlier undergone surgical repair of tracheo-esophageal fistula. He was treated with intravenous teicoplanin and gentamicin for four weeks followed by two weeks of erythromycin. No percutaneous aspiration or pleural drainage was required. He had complete clinical and radiologic recovery when seen at follow-up six months later. Aggressive antimicrobial therapy for this condition without surgical drainage resulted in complete resolution and avoided complications such as pneumothorax and bronchopleural fistula.